Efektivitas Penggunaan Media Pembelajaran Interactive Learning Berbasis ICT pada Mata Pelajaran Fiqih Kelas VIII Madrasah Tsanawiyah - Maulidiah, Elma Ainun; Nisa’, Khoirun; Wahyudi, Wahyudi (YASIN, 2025)
This study aims to design an ICT-based Interactive Learning media that can improve students' understanding of learning concepts in Fiqh material and can improve the quality of learning for teachers. The method used in this research is Research and Development (R&D) research. The development model used in this research is ADDIE including: Analysis, Design, Development, Implementation, and Evaluation. The appointed validators will assess the material aspects and media aspects where there are 2 media validators and 2 material validators. This research was conducted at MTs. Ma'arif NU Kedungkendo. The subjects of this study were students from class VIII. Data collection using media validation sheets, material validation sheets and student response questionnaires. The results of research on the development of ICT-based Interactive Learning learning media on Fiqh material produced obtained results after going through the revision and validation stage with an average score of 85% on material validation and media validation obtained an average score of 87% so that the learning media was declared very relevant and feasible to use. The student response test stage to the feasibility of learning media obtained an average score of 90% with very attractive criteria. This shows that ICT-based Interactive Learning media can be applied in the classroom and allows it to increase students' understanding of learning concepts in Fiqh material.